Paridade e simetria nos contratos empresariais : análise das regras de interpretação na Lei de liberdade econômica - Peringer, Fernanda Linden Ruaro (2022)
The present work aims to analyze the resulting change arising from law n. 13.874/2019, the Economic Freedom Law, in the business contracts’ interpretation rules in face of the creation of article 421-A, of the Civil Code, with the fundamental principles of the Economic Order of the 1988 Federal Constitution. The changes in the provisions 113 and 421, of the CC, will be briefly analyzed, as well as aspects related to the covid-19 pandemic. The study will demonstrate that the interpretation of corporate contracts is heading towards a significant readaptation where pacta sunt servanda will be valued, considerably reducing the state intervention in corporate legal business. Such law highlights that in corporate contracts will be applied a subsidiary application of the rules of corporate law, in relation to what was agreed upon, when the parties are considered symmetrical and equal, except for the legal frameworks in special laws, accodring to the final part of article 421-A of the Civil Code. Finally, we intend to emphasize the valorization of contractual freedom in the Brazilian legal system after the enactment of the Economic Freedom Law, starting from the creation of article 421-A, and, consequently, to analyze the changes of concrete effects in the jurisprudence of the Brazilian Courts.